2018
DOI: 10.1039/c7ra12030c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of graphene oxide sheets integrated with gold nanoparticles and their applications to adsorptive removal and catalytic reduction of water contaminants

Abstract: Preparation of graphene oxide–gold (GO–Au) nanocomposites as adsorbents and catalysts for decontamination of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 55 publications
(81 reference statements)
0
34
0
Order By: Relevance
“…Other studies are those reported by Liao et el. [4] (microwave modified bamboo charcoal), Rafatullah et al [5] (low cost adsorbent), Malana et al [6] (polymeric gels), El Qada et al [7] (activated carbon), Annadura et al [1] (cellulose-based waste), Malik [8] (activated carbon from wood sawdust), Halder et al [9] (thermally modified granular charcoal), Onai [10] (activated carbon prepared from apricot waste), Perira et al [11] (carbons), Tahir and Rauf [12] (bentonite clay), Vega-Negron et al [13] (chitosan/cellulose beads), Beheshti et al [14] (supramolecular complex) , Naeem et al [15] (graphene oxide sheets integrated with gold nanoparticles), Ogata et al [16] (poly-y-glutamic acid), El Alouani et al [17] (fly ashbased geopolymer), Adeyemo et al [18] (clay), etc. However, most of the reported studies on the adsorption of dyes have not paid significant attention on the potential of neem seed as an adsorbent nor fully explored detail mechanism for their adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies are those reported by Liao et el. [4] (microwave modified bamboo charcoal), Rafatullah et al [5] (low cost adsorbent), Malana et al [6] (polymeric gels), El Qada et al [7] (activated carbon), Annadura et al [1] (cellulose-based waste), Malik [8] (activated carbon from wood sawdust), Halder et al [9] (thermally modified granular charcoal), Onai [10] (activated carbon prepared from apricot waste), Perira et al [11] (carbons), Tahir and Rauf [12] (bentonite clay), Vega-Negron et al [13] (chitosan/cellulose beads), Beheshti et al [14] (supramolecular complex) , Naeem et al [15] (graphene oxide sheets integrated with gold nanoparticles), Ogata et al [16] (poly-y-glutamic acid), El Alouani et al [17] (fly ashbased geopolymer), Adeyemo et al [18] (clay), etc. However, most of the reported studies on the adsorption of dyes have not paid significant attention on the potential of neem seed as an adsorbent nor fully explored detail mechanism for their adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Naeem et al 61 integrated Au-NP onto GO sheets using modified Hummer's sol-gel technique. The procedure followed the usual technique as described by Hurtado et al 60 The morphology and photocatalytic water splitting applications showed encouraging potential.…”
Section: Sol-gel Techniquementioning
confidence: 99%
“…The distribution coefficient (K d ) used for assessing the actual performance of the prepared adsorbents was determined by this equation [41,42]:…”
Section: Adsorption Testsmentioning
confidence: 99%